Single-cell RNA sequencing to guide autologous preterm cord mesenchymal stromal cell therapy - Cyr-Depauw, Chanèle; Mižíková, Ivana; Cook, David P.; Lesage, Flore; Vadivel, Arul; Renesme, Laurent; Deng, Yupu; Zhong, Shumei; Bardin, Pauline; Xu, Liqun; Möbius, Marius A.; Marzahn, Jenny; et al. (American journal of respiratory and critical care medicine, 2025)
Rationale: The chronic lung disease bronchopulmonary dysplasia (BPD) remains the most common complication of extreme prematurity (<28 wk of gestation). Umbilical cord-derived mesenchymal stromal cells (UC-MSCs) represent an opportunity for autologous cell therapy, as UC-MSCs have been shown to improve lung function and structure in experimental BPD. However, characterization and repair capacity of UC-MSCs derived from donors with pregnancy-related complications associated with prematurity remain unexplored. - - Objectives: To characterize UC-MSCs’ transcriptome and determine if pregnancy-related complications (preeclampsia and chorioamnionitis) alter their therapeutic potential. - - Methods: Single-cell RNA sequencing was used to compare the transcriptome of UC-MSCs derived from 5 term donors, 16 preterm donors, and human neonatal dermal fibroblasts (control cells of mesenchymal origin) and correlated with their therapeutic potential in experimental BPD. Using publicly available neonatal lung single-nucleus RNA sequencing data, we also determined putative communication networks between UC-MSCs and resident lung cell populations. - - Measurements and Main Results: Most UC-MSCs displayed a similar transcriptome despite their pregnancy-related conditions and mitigated hyperoxia-induced lung injury in newborn rats. Conversely, human neonatal dermal fibroblasts and one term and two preterm with preeclampsia UC-MSC donors exhibited a distinct transcriptome enriched in genes related to fibroblast function and senescence and were devoid of therapeutic benefit in hyperoxia-induced BPD. Conversely, therapeutic UC-MSCs displayed a unique transcriptome active in cell proliferation and distinct cell-cell interactions with neonatal lung cell populations, including NEGR (neuronal growth regulator 1) and NRNX (neurexin) pathways. - - Conclusions: Term and preterm UC-MSCs are lung protective in experimental BPD. Single-cell RNA sequencing allows us to identify donors with a distinct UC-MSC transcriptome characteristic of reduced therapeutic potential.
Gesehen am 08.09.2025